180k views
1 vote
Free Response Questions12. Write a trinomial expression that is equivalent to (2x+5)(3x-2).

1 Answer

5 votes

Answer:


(2x+5)(3x-2)=6x^2+11x-10

Explanation:

To write a trinomial expression that is equivalent to the expression written above, we can use the distributive property of multiplication:


(2x+5)(3x-2)=2x\cdot3x-2x\cdot2+5\cdot3x-5\cdot2

Computing like terms, we get:


\begin{gathered} (2x+5)(3x-2)=6x^2-4x+15x-10 \\ (2x+5)(3x-2)=6x^2+11x-10 \end{gathered}

User Fruchtzwerg
by
5.4k points